A rhetorical analysis of Philippians 1: 12-26 - Snyman, A. H. (Faculty of Theology, University of the Free State, 2005)
In this article Philippians 1:12-26 is analysed from a rhetorical perspective that differs from the typical approach of researchers, who tend to force ancient rhetorical categories on a letter. The analysis is done in terms of what is called a “grounded theoretical approach”. This approach is briefly summarised, followed by a systematic analysis of Paul’s basic rhetorical strategy, as well as all the supportive rhetorical techniques in these fifteen verses. It will be argued that these verses are an integral part of Paul’s rhetorical strategy, constructed from the text itself and aimed at reassuring the Philippians that his adversities are for the advancement of the gospel. The conclusion is that a text-centred approach with its focus on the functional aspects of the text, provides a better understanding of Paul’s rhetorical strategy than a typical rhetorical analysis, with its focus on the formal aspects of the text.
Keywords: Pauline Letters; Rhetorical analysis; Philippians 1:12-26